Congenital mesenteric defect with distal ileal atresia and segmental volvulus in a neonate: A case report - Takwa Mili; Awatef charieg; Rym Ezzine; Yosra Ben Ahmed; Said Jlidi (Elsevier, 2023)
Introduction: Intestinal volvulus is a rare condition that can be life-threatening. It often occurs after birth and requires emergent surgery. Most cases of volvulus in infants and fetuses are linked to intestinal malrotation. However, Intestinal volvulus may occur even if the midgut is in normal position, due to mesenteric defects. Case presentation: We present the case of a A 2-day-old, female phenotype neonate who presented with recurrent episodes of bilious vomiting. Clinical and radiological presentation was consistent with distal intestinal atresia. In Surgical exploration, we found a segmental volvulus of the terminal ileum complicating a congenital mesenteric defect and associated with a distal ileal atresia. An ileo-caecal resection was performed as well as a resection of the dilated distal bowel. Then an ileo-colic end-to-end anastomosis was done followed by closure of the mesenteric defect. Postoperative course was uneventful. Conclusion: Mesenteric defects can lead to segmental intestinal volvulus even when the midgut is normally rotated. Treatment should be tailored according to the anatomy and bowel status of the patient.